2015
DOI: 10.17576/jsm-2015-4410-15
|View full text |Cite
|
Sign up to set email alerts
|

Anti-malarial and Anti-inflammatory Effects of Gynura procumbens are Mediated by Kaempferol via Inhibition of Glycogen Synthase Kinase-3β (GSK3β)

Abstract: Gynura procumbens is a medicinal plant, traditionally used to treat inflammation and fever. A yeast-based assay detected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…As a flavonoid, kaempferol is able to inhibit oxidative stress, ROS formation, and lipid peroxidation [2123], and there is a correlation between its antioxidant and antimalarial activities [4]. In addition, inhibition of glycogen synthase kinase-3 β (GSK3 β ) of the malaria parasite has been reported to be a molecular basis of the antimalarial effect of kaempferol [24]. GSK3 has been described to play a critical role in the host response to malaria infection [25].…”
Section: Discussionmentioning
confidence: 99%
“…As a flavonoid, kaempferol is able to inhibit oxidative stress, ROS formation, and lipid peroxidation [2123], and there is a correlation between its antioxidant and antimalarial activities [4]. In addition, inhibition of glycogen synthase kinase-3 β (GSK3 β ) of the malaria parasite has been reported to be a molecular basis of the antimalarial effect of kaempferol [24]. GSK3 has been described to play a critical role in the host response to malaria infection [25].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, G. procumbens belonging to the family Asteraceae is commonly known as longevity spinach that grows broadly in India, Bangladesh, Southeast Asia, especially in Indonesia, Malaysia, and Thailand. Some of the traditional healing claims have been verified in scientific and pharmacological studies, including anti-herpes virus [ 6 ], anti-inflammatory [ 7 , 8 ], anti-hyperlipidemic, anti-hyperglycemic [ 9 – 14 ], and anti-hypertensive activities [ 15 18 ]. Recently, particular attention has been given to G. procumbens in the pharmacology of antidiabetic medicinal plants perhaps because of its test data and efficiency in managing diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%
“…However, Jansen et al [ 77 ], reported a lack of anti-plasmodial properties of kaempferol in vitro, although the researchers isolated the molecule from medicinal plants other than those of the Asteraceae family. Kaempferol also acts as an inhibitor of glycogen synthase kinase-3β (GSK3β) of the malaria parasite [ 84 ]; hence, it blocks erythrocyte invasion by the parasite. Barlianna et al [ 85 ] confirmed the moderate anti-plasmodial properties of a derivative of kaempferol (kaempferol-3- O -rhamnoside) in P. falciparum , with a reported IC 50 value of 106 μM.…”
Section: Resultsmentioning
confidence: 99%